Recent advances of cell membrane-coated nanoparticles for therapy of bacterial infection - Song, Yue; Zheng, Xia; Hu, Juan; Ma, Subo; Li, Kun; Chen, Junyao; Xu, Xiaoling; Lu, Xiaoyang; Wang, Xiaojuan (Frontiers in Microbiology, 2023)
The rapid evolution of antibiotic resistance and the complicated bacterial infection microenvironments are serious obstacles to traditional antibiotic therapy. Developing novel antibacterial agents or strategy to prevent the occurrence of antibiotic resistance and enhance antibacterial efficiency is of the utmost importance. Cell membrane-coated nanoparticles (CM-NPs) combine the characteristics of the naturally occurring membranes with those of the synthetic core materials. CM-NPs have shown considerable promise in neutralizing toxins, evading clearance by the immune system, targeting specific bacteria, delivering antibiotics, achieving responsive antibiotic released to the microenvironments, and eradicating biofilms. Additionally, CM-NPs can be utilized in conjunction with photodynamic, sonodynamic, , and photothermal therapies. In this review, the process for preparing CM-NPs is briefly described. We focus on the functions and the recent advances in applications of several types of CM-NPs in bacterial infection, including CM-NPs derived from red blood cells, white blood cells, platelet, bacteria. CM-NPs derived from other cells, such as dendritic cells, genetically engineered cells, gastric epithelial cells and plant-derived extracellular vesicles are introduced as well. Finally, we place a novel perspective on CM-NPs’ applications in bacterial infection, and list the challenges encountered in this field from the preparation and application standpoint. We believe that advances in this technology will reduce threats posed by bacteria resistance and save lives from infectious diseases in the future.